Development Strategies for Tourism Destinations in Semarang Old Town - Retno Ginanjar; Sucihatiningsih Dian Wisika Prajanti (Economics Development Analysis Journal, 2021)
This study aims to analyze the priority strategies for developing tourism destinations in SemarangOld Town Area. This study was designed using a qualitative descriptive research method. The dataused in this study were primary and secondary data. The data collection techniques were throughinterviews, observation, documentation study, and AHP questionnaires. The data validitytechnique used in this study also used data triangulation technique, namely triangulation of sourcesand techniques. The analysis technique used in this study was to use Analysis Hierarchy Process(AHP) scheme to find an analysis of the criteria priority order from the strategies in developingtourism destinations in Semarang Old Town Area. The research results show that based on theresults of AHP analysis, the most prioritized criteria in the development strategy of tourismdestination in Semarang Old Town Area is tourism policies, followed by service criteria forvisitors in the second position, and tourism marketing criteria for the last priority. The last prioritycriterion is tourism marketing. Meanwhile, the result analysis on all alternatives shows that the firstpriority alternative is transportation control. The second priority alternative is providing a sense ofsecurity and comfort for visitors. Meanwhile, the last priority of all alternatives is the ease oflicensing to sell.